Syphilis Education for Teens as a Preventive Measure for the Spread of Sexually Transmitted Diseases in SMK Negeri 2 Medan T.A. 2024/2025 - Nasution, Irfan Sazali; Anggreyani, Selfi; Aprida, Rahmah; Putri, Dhea Fahrina; Sari, Yunita; Zannah, Wardatul; Putri, Amanda (PROMOTOR, 2025)
Sexually transmitted diseases (STDs) such as syphilis are a significant health threat among adolescents, especially due to a lack of knowledge and awareness about how to prevent them. This study aims to develop and evaluate an educational program about syphilis as a preventive measure against the spread of STDs in SMK Negeri 2 Medan. The method used was a quasi-experimental approach with a pretest-posttest design. The educational program involved delivering materials through presentations, interactive discussions, and visual media. The results showed a significant increase in the level of students' knowledge and awareness about syphilis, including how it is transmitted, its symptoms, and prevention efforts. This program also positively impacted students' attitudes toward maintaining reproductive health. This study concluded that education about syphilis is very effective as a preventive measure to reduce the risk of spreading sexually transmitted diseases (STDs) among adolescents. The recommendation from this study is the implementation of similar programs in other schools to increase adolescent awareness about sexual health more widely